Structure-Based Design, Synthesis, Biological Evaluation, and Molecular Docking of Novel PDE10 Inhibitors With Antioxidant Activities - Li, Jinxuan; Chen, Jing-Yi; Deng, Ya-Lin; Zhou, Qian; Wu, Yinuo; Wu, Deyan; Luo, Hai-Bin (Frontiers in Chemistry, 2018)
Phosphodiesterase 10 is a promising target for the treatment of a series of central nervous system (CNS) diseases. Imbalance between oxidative stress and antioxidant defense systems as a universal condition in neurodegenerative disorders is widely studied as a potential therapy for CNS diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS). To discover multifunctional pharmaceuticals as a treatment for neurodegenerative diseases, a series of quinazoline-based derivatives with PDE10 inhibitory activities and antioxidant activities were designed and synthesized. Nine out of thirteen designed compounds showed good PDE10 inhibition at the concentration of 1.0 μM. Among these compounds, eight exhibited moderate to excellent antioxidant activity with ORAC (oxygen radical absorbance capacity) value above 1.0. Molecular docking was performed for better understanding of the binding patterns of these compounds with PDE10. Compound 11e, which showed remarkable inhibitory activity against PDE10 and antioxidant activity may serve as a lead for the further modification.